Development of Henneguya zschokkei (Myxozoa: Myxosporea) actinospores in oligochaetes and plasmodia in whitefish Coregonous lavaretus - Osman, Zul Faizuddin (2013)
The aim of this study was to describe the life cycle of H. zschokkei by observing the development of actinospores in oligochaete and the morphological development of H. zschokkei cysts in whitefish. Laboratory observation of seasonal occurrence of actinospores sampled from oligochaetes from RTKL Tervo Fish Farm revealed 6 types of actinospores from collective groups of Triactinomyxon, Raabeia and Aurantiactinomyxon in 2010, and 3 types of actinospores in 2011. Both years showed similar patterns with the release of actinospores peaking in both summer (June and July) and winter (January and February) times. The infection experiment was not successful in infecting Coregonus lavaretus with myxozoan parasite Henneguya zschokkei. In addition, 336 individuals of whitefish C. lavaretus from fish farm were examined to study the factors influencing the prevalence and intensity of infection of H. zschokkei. Three types of cysts were observed in this study namely cyst type-1 (mature plasmodium cyst), cyst type-2 (intermediate plasmodium cyst) and cyst type-3 (immature cyst). A pattern was observed with high prevalence of type 3 cyst (small cyst without myxospore) in young C. lavaretus and high prevalence of type-1 cyst in older C. lavaretus. Melanisation of cysts were also observed especially in older C. lavaretus. The prevalence of H. zschokkei was influenced by host age (42.0 % in 2 year old; 0.7 % in 1 year old) and host size but not by host sex. Based on these findings, the prevalence of H. zschokkei infection and the development of cyst were associated with host age.